Selection and recommend of quinoa (Chenopodium quinoa) genotypes based on the yield genotypic adaptability and stability - Soares de Vasconcelos, Edmar; de Moraes Echer, Marcia; Kliemann, Marcio André; Lang, Marcelo Júnior (Revista Ceres, 2025)
The present study aimed to select and recommend quinoa genotypes based on the yield genotypic adaptability and stability, by the method of the Harmonic mean of relative performance of genotypic values. Five experiments were conducted during the crop seasons of 2014 and 2015 in two locations in the Western region of Paraná State, Brazil. This study involved the evaluation of the yield of thirteen quinoa genotypes. Initially, the genotypic values (GV) were obtained by employing BLUP/REML methodology for mixed models. After, the values of the harmonic mean for genotypic value (HMGV*MG), the relative performance for genotypic values (RPGV*MG) and the harmonic mean of the relative performance for genotypic values (HMRPGV*MG) were obtained. The genotypes Q1317 and Q2014 were the best indicated for cultivation in the summer crop, with medium yield genotypic stability and adaptability. The genotype Q1318 is recommended for winter crop, presenting high yield genotypic stability and adaptability.